2022
DOI: 10.3390/chemengineering6010016
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Model for Thermal Treatment of Sewage Sludge

Abstract: Sewage sludge is here studied as a valuable source for processing or energy conversation thanks to its high nutrition and energy content. However, various origins of the wastewater, different water cleaning technologies, and seasonal and regional dependencies lead to the high variability of the sewage sludge properties. In thermal treatment units, that is, incineration, gasification and pyrolysis, sewage sludge serves as feedstock or fuel, hence a proper characterization and a mathematical description of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…In Europe, the most popular bedding materials are straw, wood carvings, or sawdust, but in the USA, the most recommended bedding material is sand, which unquestionably elevates the ash content, as Nam et al reported the ash content of dairy cattle manure with sand bedding to be 48.8 ± 3.1% [78]. High ash content positions animal manure closer to sewage sludge than plant-origin biomass [79][80][81][82].…”
Section: Ash Contentmentioning
confidence: 99%
“…In Europe, the most popular bedding materials are straw, wood carvings, or sawdust, but in the USA, the most recommended bedding material is sand, which unquestionably elevates the ash content, as Nam et al reported the ash content of dairy cattle manure with sand bedding to be 48.8 ± 3.1% [78]. High ash content positions animal manure closer to sewage sludge than plant-origin biomass [79][80][81][82].…”
Section: Ash Contentmentioning
confidence: 99%
“…For instance, Wang et al [ 35 ] revealed that increasing retention time from 1hr to 2.5hrs resulted in biochar yield decline from 52% to 45%. Moreover, very few mathematical models are proposed to describe sewage sludge pyrolysis process due to complexity and variability of sludge characteristics [ 36 ]. Hence, further research is required to explore the influence of various parameters on sludge pyrolysis before it can be effectively modeled.…”
Section: Introductionmentioning
confidence: 99%
“…A frequently used natural reagent is lignocellulosic biomass. The use of lignocellulosic materials is particularly justified due to the calorific value and energetic processing of sludge, such as incineration, gasification, pyrolysis, as feedstock or fuel [26] and carbonisation [27]. Cellulose is also treated as a structure-forming material that reduces sludge compressibility.…”
Section: Introductionmentioning
confidence: 99%